Strategy to Optimize Nurse Credentials in Hospitals - Asiana Oktavia Purwaningsih; Ahsan; Tita Hariyanti (Journal Of Nursing Practice, 2025)
Background: Profession nursing keep going improve and try creating governance​ good clinical to be able to face various type change as well as demands society. One of the efforts made​ profession nursing is with improvement level career through credentials at home sick. Activities evaluation competence nursing is very important for give maintenance competent patient​ based on evidence and hold on stick to the code ethics profession. Purpose: The purpose of credentials is increase accountability nurse, improve satisfaction, and create stability in a organization. Methods: Protocol this developed in line with the Joanna Briggs Institute (JBI) methodology for inspection scoping and reporting in accordance with Reporting Items Choice for Review Systematic and Meta-analysis Protocol (PRISMA-P). The literature conducted analysis consists of from ProQuest, Ebsco, Science direct, Elsevier from 2015 to​ 2023. Results: manager​ nurse have role big in increase implementation level career use increase quality service. Conclusion: The career level program, supported by impactful mentoring and strong nurse manager involvement, enhances nurses' career development and job satisfaction. Through effective credentialing, nursing competence is ensured, reducing clinical errors and minimizing risks to patient safety.